Effect of amphoteric and cationic polyacrylamide on the structural and strength properties of coir paper - Main, Nor Mazlana; A.Talib, Rosnita; Abdul Rahman, Russly; Mohamed, Ainun Zuriyati; Ibrahim, Rushdan; Adnan, Sharmiza (Elsevier, 2015)
This study explores the benefits of using Amphoteric PAM (aPAM) and Cationic PAM (cPAM) as a dry strength agent in coir based paper. The aPAM and cPAM were incorporated to coir pulp slurry in different dosages (0.5% - 2.0%) during stock preparation. Industrial grade of potassium aluminum sulfate (alum) was used for all sets handsheet. For each treatment, 12 handsheets, each having basis weight of 120 g/m2 were made. The results showed that the utilization of cPAM had better drainage compared to the aPAM for all treatment. In general, the apparent density and strength properties were significantly affected by the addition of dry strength agents. The enhancing effect of aPAM on strength properties of coir paper was much higher than using cPAM except for ring crush test (RCT) and concora medium test (CMT).